2015
DOI: 10.1089/jop.2014.0090
|View full text |Cite
|
Sign up to set email alerts
|

A Study Comparing Standard and Transepithelial Collagen Cross-Linking Riboflavin Solutions: Epithelial Findings and Pain Scores

Abstract: The epithelial damage was observed in both procedures; also, the epithelial healing time was longer in Epi-on CCL and it is of great importance that the patients should have therapeutic contact lenses until the epithelium heals in both procedures. The Epi-off CCL group had less pain scores than the Epi-on CCL group and more pain problems after Epi-on CCL still remains. The patient should be informed about pain, even if the Epi-on CCL procedure was performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
1
9
0
3
Order By: Relevance
“…Not only did 24% of eyes in this series progress with an increase in Kmax greater than 1.0 D at 12 months, but almost 50% of eyes had epithelial defects on the first day due to epithelial toxicity from prolonged BAC application. Such findings of epithelial damage are consistent with the study by Yuksel et al (119), who found higher pain scores on day 1 and longer epithelialization times with epithelium-on treatments.…”
Section: Epithelium-on Cxl: Chemical Enhancerssupporting
confidence: 92%
“…Not only did 24% of eyes in this series progress with an increase in Kmax greater than 1.0 D at 12 months, but almost 50% of eyes had epithelial defects on the first day due to epithelial toxicity from prolonged BAC application. Such findings of epithelial damage are consistent with the study by Yuksel et al (119), who found higher pain scores on day 1 and longer epithelialization times with epithelium-on treatments.…”
Section: Epithelium-on Cxl: Chemical Enhancerssupporting
confidence: 92%
“…Additionally, epi-off CXL increases the risk of complications including pain, corneal haze, corneal melt, infection, and endothelial decompensation. [8][9][10][11][12][13][14][15] For these reasons, there is an incentive to perform epi-on CXL.…”
Section: Discussionmentioning
confidence: 99%
“…37 Moreover, epithelial disruption or postoperative epithelial sloughing with some permeation enhancers (eg, benzalkonium chloride) or iontophoresis leads to inadvertent partial or complete epi-off procedures. [38][39][40] Other alternative approaches such as injection of riboflavin solution into an intrastromal pocket, 41,42 topical application of riboflavin nanoemulsions [43][44][45] or oral administration of riboflavin followed by sunlight exposure 46 still await confirmation of effectiveness.…”
Section: Introductionmentioning
confidence: 99%